Desmopressin in non‐severe haemophilia A: Test‐response and clinical outcomes in a single Canadian centre review. Issue 5 (13th July 2018) - Hews‐Girard, Julia; Rydz, Natalia; Lee, Adrienne; Goodyear, Marilyn Dawn; Poon, Man‐Chiu
Abstract : Introduction: Desmopressin is an effective haemostatic agent for patients with non‐severe haemophilia A; however, response may differ between patients of similar severity. Responsiveness is classified based on various cut‐off values for plasma levels of FVIII post‐desmopressin administration. Patients may be classified differently depending on the values chosen. Aim: To classify desmopressin response in non‐severe haemophilia A patients with respect to current test‐response definitions. Also, to characterize relationships between test response and clinical outcome of desmopressin use. Methods: Current desmopressin test‐response definitions were obtained from the literature. We adopted peak FVIII level (at 1 hour post‐administration) ≥50 IU/dL and <20 IU/dL as complete and no response, respectively, thereby satisfying most reported definitions. Test‐responses and clinical outcomes of use between 2007 and 2017 for adult mild/moderate haemophilia A patients were reviewed and correlated. Results: All patients classified as complete responders (n = 31; peak FVIII ≥50 IU/dL) and the majority of partial responders (n = 11; peak FVIII ≥20 to <50 IU/dL) had good clinical outcomes after desmopressin use for a variety of bleeding episodes and procedures. Two non‐responders (peak FVIII <20 IU/dL) given desmopressin for minor bleeding/procedures also had good clinical outcomes. One patient with a partial test‐response (peak FVIII 23 IU/dL) required additional factor concentrate to achieve haemostasis. Conclusions: Based on our review, we suggest that the determination of desmopressin responsiveness should consider both the change in plasma FVIII levels as well as clinical outcomes associated with prior therapeutic use.